2017
DOI: 10.18632/oncotarget.15717
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open radical cystectomy for patients with bladder cancer over 75-year-old: a prospective randomized controlled trial

Abstract: The aim of this study was to compare the morbidity, mortality, oncological results and quality of life between laparoscopic radical cystectomy (LRC) and open radical cystectomy (ORC) in the elderly patients over 75 years old. Between January 2012 and January 2015, 60 patients were recruited into this study, who were randomly assigned in a 1:1 ratio to either LRC or ORC group. Baseline patient characteristics, pathological factors, operative and postoperative characteristics, postoperative complications and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…For MIS approaches, 83 patients underwent LRC and the remaining 431 patients underwent RARC. And 5 studies compared RARC with ORC [14,15,18,20,21], 2 studies compared LRC with ORC [16,19], 1 study was a three-arm trial of ORC, LRC, and RARC [17]. The sample sizes of included studies were relatively small and only 1 study included more than 150 patients [14].…”
Section: Clinical Characteristics Of Enrolled Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For MIS approaches, 83 patients underwent LRC and the remaining 431 patients underwent RARC. And 5 studies compared RARC with ORC [14,15,18,20,21], 2 studies compared LRC with ORC [16,19], 1 study was a three-arm trial of ORC, LRC, and RARC [17]. The sample sizes of included studies were relatively small and only 1 study included more than 150 patients [14].…”
Section: Clinical Characteristics Of Enrolled Studiesmentioning
confidence: 99%
“…Two studies included the same cohort patients, but one study reported the perioperative outcome [18], the other one reported the long-term outcomes [15]. As for the duration of follow-up, 3 studies did not reveal relevant information [18,20,21], 4 studies had a middle-term follow-up [14,16,17,19], and 1 study had a relatively long follow-up, the median duration is 4.9 years [15]. Four studies reported the rates of neoadjuvant chemotherapy (NAC), 27.5% of MIS patients used the NAC, and 36.8% of ORC patients used the NAC.…”
Section: Clinical Characteristics Of Enrolled Studiesmentioning
confidence: 99%
“…Thirteen articles lacked useful data and were not RCTs. Finally, eight articles reporting data from a total of nine RCTs (803 patients) [17][18][19][20][21][22][23][24] were included in the meta-analysis: six RCTs compared RARC with ORC, and three RCTs compared LRC with ORC. The baseline characteristics of the studies included in our meta-analysis are listed in Table 1.…”
Section: Characteristics Of the Individual Studiesmentioning
confidence: 99%
“…Five articles (21)(22)(23)25,27) reported on IBL in the LRC and ORC groups. A total of 370 patients with BC were included, with 178 cases in the LRC group and 192 in the ORC group.…”
Section: Iblmentioning
confidence: 99%
“…Three articles (22,27,28) and P=0.08) indicated that there was heterogeneity among the studies, and therefore, the research data were analyzed using the REM. Figure 6 shows the analysis results.…”
Section: Intraoperative Blood Transfusion Ratementioning
confidence: 99%